Activities of merchant bank and a comparative analysis of City Bank Capital Resources Limited, BRAC EPL investment, Lankabangla investment, Prime Bank investment and IDLC investment - Mou, Mahiya Mohosi (BRAC University, 2018)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2017.